Comparison of methylation resistant and sensitive CpG islands using DNA sequence information content - Shivangi (My University, 2016)
The organization of eukaryotic DNA is highly diversified and it includes certain CpG rich sequences called CpG islands. These CpG islands are found to be unmethylated usually. The methylation is occurs at the dinucleotide CpG. Most of the CpG islands are known to be associated with the promoter region of the genes and are usually unmethylated. Lately, it has been found out that CpG Islands exhibit varying propensity to get methylated. They can be fully methylated or unmethylated, thereby may be considered as methylation sensitive or methylation resistant. In the present work, a comparative study of the methylation sensitive and methylation resistant is done based on the two attributes i.e., randomness and compression. Both the attributes were statistically analyzed and thus the result can be speculated to influence the methylation of CpG Islands.
Keywords: Methylation; CpG islands; Epigenetics; Randomness; Compression